Mechanisms Linking Colorectal Cancer to the Consumption of (Processed) Red Meat: A Review. Issue 16 (9th December 2016) - Demeyer, Daniel; Mertens, Birgit; De Smet, Stefaan; Ulens, Michèle
Abstract : Colorectal cancer (CRC) is the third most commonly diagnosed cancer in the world. The vast majority of CRC cases have been linked to environmental causes rather than to heritable genetic changes. Over the last decades, epidemiological evidence linking the consumption of red and, more convincingly, of processed red meat to CRC has accumulated. In parallel, hypotheses on carcinogenic mechanisms underlying an association between CRC and the intake of red and processed red meat have been proposed and investigated in biological studies. The hypotheses that have received most attention until now include (1) the presence of polycyclic aromatic hydrocarbons and heterocyclic aromatic amines, two groups of compounds recognized as carcinogenic, (2) the enhancing effect of (nitrosyl)heme on the formation of carcinogenic N-nitroso compounds and lipid peroxidation. However, none of these hypotheses completely explains the link between red and processed red meat intake and the CRC risk. Consequently, scientists have proposed additional mechanisms or refined their hypotheses. This review first briefly summarizes the development of CRC followed by an in-depth overview and critical discussion of the different potential carcinogenic mechanisms underlying the increased CRC risk associated with the consumption of red and processed red meat.